Implementation of Inclusive Education Under the Convention on the Rights of Disabled People: A Comparative Legal Aspect - Lebed, Anna V.; Guseva, Anna A.; Karabutov, Alexander A.; Markhgeym, Marina V.; Rusin, Ivan A. (Cuestiones Políticas, 2020)
The article presents a comparative analysis of inclusive education training in the Russian Federation, Germany and Italy based on the analysis of the provisions of the United Nations Convention on the Rights of Persons with Disabilities, also related to the development of inclusive education in member countries. At a methodological level, the study was built on the basis of a dialectical approach to the study of legal phenomena and processes, using a general intellectual process for the processing of sources of type: (systemic, logical, analysis and synthesis), all within the framework of documentary observation close to legal hermeneutics. The study of the concluding observations on the initial report of the states participating in the Convention mentioned above allows concluding that the approaches to inclusion are heterogeneous in different countries of Western Europe before signing and ratifying the United Nations Convention on the rights of People with disabilities. Furthermore, the document sought to determine the level of development of inclusive education, its problems and prospects in Russia compared to the states of Western Europe.